A Candidate Gene Approach to ANCA-Associated Vasculitis Reveals Links to the C3 and CTLA-4 Genes but not to the IL1-Ra And Fcγ-RIIa Genes - Ulf Persson; Birgitta Gullstrand; Åsa Pettersson; Gunnar Sturfelt; Lennart Truedsson; Mårten Segelmark (Karger Publishers, 2013)
Background/Aims: The aim of the study is to search for associations between Antineutrophil cytoplasm antibody (ANCA)-associated vasculitis (AAV) and polymorphisms in the genes of four key molecules possibly involved in different pathogenic pathways; complement C3, CTLA-4, Fcγ-RIIa and IL1-Ra. Patients and Methods: Patients with AAV (n=105) subgrouped as microscopic polyangiitis or granulomatosis with polyangiitis (Wegener's granulomatosis) and myeloperoxidase (MPO) or proteinase 3 (PR3) ANCA positive were compared to a control group of 200 blood donors. Polymorphisms in the genes were analysed with PCR amplification of DNA. Results: The diagnosis of AAV was confirmed in the 105 cases. The gene frequency of C3F was 0.27 in the PR3-ANCA subgroup (p=0.041) compared to 0,19 in the control group. The number of patients homozygous for the shortest 86 bp allele of CTLA-4 was significantly decreased in the whole group of patients (p=0.049). No differences were evident in the Fcγ-RIIa and IL1-Ra polymorphisms when compared to controls, neither in the whole group of patients, nor in any of the sub-groups. Conclusion: The aberrant gene frequency of the C3F allele among PR3-ANCA positive patients and the findings with the CTLA-4 polymorphism indicates that complement may be involved in pathogenesis and that T-cell activation also is of importance in these diseases.